American masterworks : houses of the 20th and 21st centuries - Frampton, Kenneth. 4 0 16; 1936- Larkin, David; 5 (New York : Rizzoli, 2008)
Photographs and text examine forty-four American residential structures of the twentieth and twenty-first centuries, and features home designs by Frank Lloyd Wright, Frank Gehry, Zoka Zola, and many others.
Includes bibliographical references (p. 381).
Adult;Adult
Keywords: 2 -- 0; 6; History;History -- Architecture, Domestic;Architecture;Architecture;Domestic architecture;Architecture;Architecture -- United States.;United States;United States;United States.;United States.;United States. -- 20th century.;21st century.;20th century;21st century; 20; 2